Proyecto de factibilidad para la creación de una empresa dedicada a la producción y comercialización de material publicitario (pop) para Instituciones Educativas y empresariales en la ciudad de Latacunga. - Bautista Hinojosa, Lorena Alexandra (2013)
In the Market Study determined the demand, offer the product under study and its projections, analysis is focused on the existing businesses and educational institutions in the Canton Latacunga, we also analyze the marketing strategy of the product, in the technical study analyzed the factors determining the size of the project and its optimal location in the target market through the study of the infrastructure and resources needed to strategically align our company, Project Engineering determines the necessary requirements of materials, human and other resources that are generated when starting a business, Legal Study chapter determines the creation of rules and regulations according to the nature and economic activity Organizational Study project for creating a functional structure to facilitate the relationship between human resource and get more efficiency. The